Praktik Pembelajaran Keterampilan Berbicara Di Masa Pandemi Covid-19 - Rizki Amalia Sholihah (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2020)
This study aims to describe the practice of language learning, namely the speaking ability of students during the pandemic period with a learning system that dares to follow what they face. The subjects in this study were 13 students of PGMI Insuri Ponorogo. The practice of learning Speaking skills is carried out with four speaking practices: reading stories, reading announcements, making speeches, and discussing. Of the four practices, knew that if you do not practice speaking, namely reading stories, reading announcements, and making speeches, it only folds four aspects of delivery, namely (1) vocal clarity; (2) correct intonation; (3) accuracy of word choice (diction); and (4) sentence structure (speech). There is no interaction with other speakers, no need to convey or express opinions, and not required to show data outside of the text to support their speaking skills. In contrast to the ability to discuss which requires six aspects, namely (1) fluency in delivering responses/responses; (2) vocal clarity; (3) correct intonation; (4) accuracy of word choice (diction); (5) sentence structure (speech); and (6) accuracy in disclosing data in practice. In the discussion practice, the students' ability to speak is also better without reading texts. However, it cannot involve one aspect of learning services from voice message media.. be involved, namely eye contact with listeners. One aspect of this also later becomes one of the pathways related to bold learning that only uses voice message media in learning. Not recognizing expressions and gestures when executing the practice also prevents listeners from entering into reports.